PANCASILA SEBAGAI LANDASAN ILMU PILAR KEILMUAN INDONESIA - Tarihoran, Haikal Ariqoh (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Pancasila as the basis of the state, is not only a state symbol, but also a philosophical system that should guide the direction of research and shape the character of scientists. This abstract analyzes the implications of each Pancasila principle for the development of science, emphasizing the importance of ethics, humanity, unity, democracy and justice in the research process and application of science for the progress of a civilized and just Indonesian nation. Furthermore, this Abstract discusses the challenges in implementing Pancasila values ​​in research practice, such as potential conflicts of interest and the need for effective monitoring mechanisms. This research concludes that the implementation of Pancasila values ​​in science is crucial to ensure science contributes positively to Indonesia's prosperity and progress, and requires joint commitment from all stakeholders. This research examines how the noble values ​​of Pancasila such as Belief in One Almighty God, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Deliberation/Representation, and Social Justice for All Indonesian People can be implemented in the process of development, implementation, and science evaluation.